2016
DOI: 10.1155/2016/1216258
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Locomotor Training after Spinal Cord Injury: Reorganization of Spinal Neuronal Circuits and Recovery of Motor Function

Abstract: Locomotor training is a classic rehabilitation approach utilized with the aim of improving sensorimotor function and walking ability in people with spinal cord injury (SCI). Recent studies have provided strong evidence that locomotor training of persons with clinically complete, motor complete, or motor incomplete SCI induces functional reorganization of spinal neuronal networks at multisegmental levels at rest and during assisted stepping. This neuronal reorganization coincides with improvements in motor func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 199 publications
(220 reference statements)
1
65
0
2
Order By: Relevance
“…Mechanisms underlying improved kinematic coordination deserves further study, but suggests altered neural strategies underlie the observed changes. Indeed, stepping training has been shown to elicit increases in supraspinal 51 and spinal circuits 52 that may contribute to locomotor improvements. These changes may be enhanced with high-intensity training, which can result in the synthesis and release of various trophic factors (e.g., brain-derived neurotrophic factors, or BDNF; for review, please see 53,54 ) that may facilitate neuroplastic alterations 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying improved kinematic coordination deserves further study, but suggests altered neural strategies underlie the observed changes. Indeed, stepping training has been shown to elicit increases in supraspinal 51 and spinal circuits 52 that may contribute to locomotor improvements. These changes may be enhanced with high-intensity training, which can result in the synthesis and release of various trophic factors (e.g., brain-derived neurotrophic factors, or BDNF; for review, please see 53,54 ) that may facilitate neuroplastic alterations 40 .…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms include clonus or hyper-reflexive response to afferent input (i.e., stretch, touch, cold temperatures), muscle stiffness (hypertonia), and spontaneous involuntary muscle contractions (spasms) (17,18). The maladaptive changes to the circuits controlling the DF and PF following SCI have been described (19)(20)(21); however, Abbreviations: SCI, spinal cord injury; DF, ankle dorsiflexors; VAC, volitional ankle control; SRC, spinal reflex circuitry; CST, corticospinal tract; H-reflex, Hoffman reflex; MEP, motor evoked potentials; PF, plantar flexors; TMS, transcranial magnetic stimulation. the relationship between decreased CST descending drive and disrupted SRC modulation with volitional ankle control (VAC) (dorsiflexion during gait, toe tapping, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord transection is surgically performed around the mid-thoracic level, which removes descending input to MNs below that level. After spinal cord transection, the biophysical properties of MNs below the site of the insult undergo significant changes (Smith and Knikou 2016). However, intracellular recordings from cat and rat MNs reveal a paradoxical effect of spinal cord transection on MN excitability.…”
Section: Spinal Cord Injurymentioning
confidence: 98%